The Effect of a Proposed Training Program for Developing Core, Arm, and Leg Muscle Strength on the Time Performance of Middle-Distance Swimmers - Maan Hasan Mahmood, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. This study examines whether a targeted strength program for the core, arms, and legs can improve middle-distance swimming performance time. Specifically, it evaluates changes in (1) core strength, (2) arm strength, (3) leg strength, and (4) overall time performance in youth middle-distance swimmers.Materials and Methods. An experimental method with a pre-test–post-test control group design was used. Participants were 45 youth-category swimmers, randomly selected from several sports groups in Kirkuk Governorate. They were divided into an experimental group and a control group. The experimental group followed a specialized, integrated strength program focusing on the core, arms, and legs, while the control group continued with regular training.Results. Swimmers who completed the specialized strength exercises showed better time performance than those who only followed the usual training. Post-test comparisons also indicated a statistically significant advantage for the experimental group across all measured variables.  Conclusions. It summarizes and wraps up the ideas, presenting the key findings and insights derived from your study. It should include a concise summary of the main points discussed in the paper, including the research objectives, methodology, and results.